2015
DOI: 10.1093/jisesa/iev025
|View full text |Cite
|
Sign up to set email alerts
|

Creams Formulated with Ocimum gratissimum L. and Lantana camara L. Crude Extracts and Fractions as Mosquito Repellents Against Aedes aegypti L. (Diptera: Culicidae)

Abstract: Mosquitoes are the most deadly vectors of parasites that cause diseases such as malaria, yellow fever, and filariasis. In view of the recent increased interest in developing plant origin insecticides as an alternative to chemical insecticides, the objective of this study was to determine the repellent activity of creams formulated with methanol crude extract (MCE), hexane fraction (HF), and ethyl acetate fractions (EAFs) of Ocimum gratissimum and Lantana camara leaves in single and combined actions against fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
4
12
0
2
Order By: Relevance
“…Treatments were performed in cages (30 × 30 cm) made of white cotton cloth with two openings (15 cm diameter) on either side. The extract was formulated as previously described [51], and DEET (N,N-diethyl-3-methylbenzamide) was taken as a positive control. Hands were entirely covered with three layers of latex gloves.…”
Section: Bioassaymentioning
confidence: 99%
“…Treatments were performed in cages (30 × 30 cm) made of white cotton cloth with two openings (15 cm diameter) on either side. The extract was formulated as previously described [51], and DEET (N,N-diethyl-3-methylbenzamide) was taken as a positive control. Hands were entirely covered with three layers of latex gloves.…”
Section: Bioassaymentioning
confidence: 99%
“…This indicates that the P. aduncum EO in semisolid formulations is as effective as the synthetic repellent PMD at repelling mosquitoes since the EO could repel >80% of the mosquitoes for more than 2 h. All the semisolid formulations were able to repel >65% of the mosquitoes 4 h post-application. In contrast, a recent study showed that a cream formulation containing Lantana camara Linnaeus methanol crude extracts and hexane and ethyl acetate fractions could only repel >60% of the mosquitoes up to 2.5 h post-application (Keziah et al , 2015).…”
Section: Discussionmentioning
confidence: 95%
“…The repellent effects were based on the strength of the extracts and fractions. Methanol crude extracts combination and hexane fractions mixtures from both plants showed synergistic effect [60].…”
Section: Antiparasitic Effectsmentioning
confidence: 99%